Chicken lysozyme gene contains several intervening sequences. - Nguyen-Huu, M C (1979)
The organization of the chicken lysozyme gene and its neighboring sequences was examined by a comparison of the restriction map of the lysozyme structural gene with the map of the lysozyme gene in genomic DNA. Chicken DNA was cleaved with restriction endonucleases and the DNA fragments were separated by agarose gel electrophoresis. After transfer of the fragments onto nitrocellulose filters, those fragments that contain lysozyme mRNA sequences were detected by hybridization of the filters to labeled probes generated from pls-1, a recombinant plasmid carrying the lysozyme structural gene. This analysis revealed the presence of at least three intervening sequences, two of which interrupt the protein coding region and one of which is located in the 3' untranslated region. When oviduct DNA and sperm DNA were compared, no difference was observed in the size and number of restriction fragments that contain either lysozyme or ovalbumin structural gene sequences.